Green Lifestyle, Green Promotion, and Demographic Characteristics on Green Housing Purchase Intention - Wardana, Nandi; Shiratina, Aldina (ARE Publisher, 2026)
Objectives: This study aims to examine the effects of Green Lifestyle, Green Promotion, and Demographic Characteristics on Green Purchase Intention, with Green Trust as a mediating variable, in the context of green housing projects developed by Perum Perumnas in West Java, Indonesia. Methodology: This research employs a quantitative approach using a survey method, with data collected from consumers who have an interest in purchasing green housing developed by Perumnas. The collected data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both direct and mediating relationships among the research variables. Finding: The results indicate that Green Promotion has a positive and significant effect on Green Trust and Green Purchase Intention. Green Trust also has a significant effect on Green Purchase Intention. Demographic Characteristics are found to have a significant effect on Green Purchase Intentionbut do not significantly influence Green Trust. Meanwhile, Green Lifestyle does not have a significant effect on either Green Trust or Green Purchase Intention. Mediation analysis shows that Green Trust only mediates the relationship between Green Promotion and Green Purchase Intention. Conclusion: This study concludes that in high-involvement purchasing decisions such as green housing, Green Promotion and Green Trust play a more critical role in shaping Green Purchase Intentionthan Green Lifestyle or Demographic Characteristics.